Influence of fertilizer rates, planting density and light transmittance on yield and quality of P. cyrtonema - Yuanwei Deng; Ni Guo; Yamin Liu (International Journal of Agricultural Sustainability)
P. cyrtonema is an important medicinal plant in China, but rising market demand has highlighted the need for improved cultivation practices. Planting P. cyrtonema under tree shade is proposed as a sustainable method, yet technological and agronomic gaps remain in optimizing growth and productivity. Hence there is a need to develop efficient cultivation strategies to improve both yield and quality of P. cyrtonema, which will ensure its continuous availability to meet rising market demands. With this background the study has been carried out with the following objective of evaluating the growth, yield, and quality of P. cyrtonema, with different treatments of fertilizer application, planting density, and light transmittance. The results showed that nitrogen (N) is the most limiting factor for yield, followed by potassium (K) and phosphorus (P). The interaction effects ranked as NP > PK > NK. A combination of 50%–75% organic fertilizer significantly improved yield and quality. The optimal planting density was found to be 25 cm × 40 cm, and the ideal light transmittance range was 45.7%–68.4%. These findings provide strategic solutions for enhancing the productivity of P. cyrtonema and developing sustainable cultivation techniques, helping to reduce the supply-demand gap for this medicinal plant.